Island, Neosho County - Beardmore, Tyler (Kansas State University, The Chapman Center for Rural Studies, 2015)
While it may be unrecorded, Island, Lincoln Township, Neosho County, Kansas, is still talked about today. This study discusses the factors that played a role in the collapse of Island, mostly due to its location and geography. I used county histories, newspapers, and census data.
Tyler Beardmore, “Island, Neosho County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/163.
Keywords: Big Island; Chanute; Island; Jacksonville; Neosho County; Valley City Cemetery